Career Maturity in High School Students: The Interplay of Self Efficacy and Locus of Control - Dandi Prayoga; Najlatun Naqiyah; Ari Khusumadewi; Wiryo Nuryono; Dian Oktaviana (Indonesian Journal of Guidance and Counseling: Theory and Application, 2024)
The research is motivated by the need for career maturity to help students choose the right educational path, as many students lack readiness. This is due to low career planning skills, limited knowledge about further education and the workforce, and the tendency to follow peers' choices without considering their own potential. Using a quantitative approach with an ex post facto correlational design, the study involved a population of 4,383 students with a sample of 367 students selected through cluster random sampling. The instruments used include Career Maturity Inventory (validity 0.306-0.610, reliability 0.734), General Self efficacy (validity 0.488-0.748, reliability 0.850), and Rotter's Locus of control (validity 0.153-0.791, reliability 0.911). Data were analyzed using Kendall's Tau and Kendall's W techniques. The results showed a significant relationship between “self efficacy” and career maturity (p = 0.000, r = 0.387), locus of control and career maturity (p = 0.000, r = 0.137), and a significant relationship between “self efficacy” and locus of control with career maturity (p = 0.000, W = 0.755). The findings confirm that “self efficacy” and belief in locus of control significantly affect career maturity. The role of counseling teachers is needed in supporting the development of students' self-efficacy and locus of control through directed and continuous counseling services, and this research encourages the development of holistic career guidance programs and further research on external factors. Tujuan penelitian ini mengkaji keterkaitan antara “self efficacy” dan “locus of control” dengan kematangan karier siswa SMA. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis ex post facto melalui desain korelasional, yang memiliki populasi 4.383 siswa dengan sampel 367 siswa yang dipilih melalui stratified random sampling. Instrumen yang digunakan meliputi Career Maturity Inventory (validitas 0,306–0,610, reliabilitas 0,734), General Self efficacy (validitas 0,488–0,748, reliabilitas 0,850), dan Rotter's Locus of control (validitas 0,153–0,791, reliabilitas 0,911). Analisis data dilakukan dengan teknik Kendall’s Tau dan Kendall’s W. Hasil penelitian menunjukkan adanya hubungan signifikan antara self efficacy dan kematangan karier (p = 0,000, r = 0,387), locus of control dan kematangan karier (p = 0,000, r = 0,137), serta hubungan signifikan antara self efficacy dan locus of control dengan kematangan karier (p = 0,000, W = 0,755). Temuan ini menegaskan bahwasanya percaya diri dan keyakinan terhadap kontrol diri sangat memengaruhi kesiapan karier. Peran guru BK dibutuhkan dalam mendukung pengembangan self efficacy dan locus of control siswa melalui layanan konseling yang terarah dan berkesinambungan, serta penelitian ini mendorong pengembangan program bimbingan karier holistik dan penelitian lanjutan mengenai faktor eksternal.